9(3c-1)-2=25c+9

Simple and best practice solution for 9(3c-1)-2=25c+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3c-1)-2=25c+9 equation:


Simplifying
9(3c + -1) + -2 = 25c + 9

Reorder the terms:
9(-1 + 3c) + -2 = 25c + 9
(-1 * 9 + 3c * 9) + -2 = 25c + 9
(-9 + 27c) + -2 = 25c + 9

Reorder the terms:
-9 + -2 + 27c = 25c + 9

Combine like terms: -9 + -2 = -11
-11 + 27c = 25c + 9

Reorder the terms:
-11 + 27c = 9 + 25c

Solving
-11 + 27c = 9 + 25c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-25c' to each side of the equation.
-11 + 27c + -25c = 9 + 25c + -25c

Combine like terms: 27c + -25c = 2c
-11 + 2c = 9 + 25c + -25c

Combine like terms: 25c + -25c = 0
-11 + 2c = 9 + 0
-11 + 2c = 9

Add '11' to each side of the equation.
-11 + 11 + 2c = 9 + 11

Combine like terms: -11 + 11 = 0
0 + 2c = 9 + 11
2c = 9 + 11

Combine like terms: 9 + 11 = 20
2c = 20

Divide each side by '2'.
c = 10

Simplifying
c = 10

See similar equations:

| 2(2z-3)-2(3-4z)=2 | | 3(2z-2)-3(3-4z)=6 | | 11/8x22/8 | | 17=193-v | | 12+2(z-6)=-6z+1 | | -w+49=245 | | 6675=29(175) | | -7(n+2)+15=-3n-19 | | -2+3x=-11+4x | | -2+3x=-11+4c | | 8x=x-18 | | 1x+9=12+3x | | a-2/3=-4/5 | | 1x+9=12+12x | | 7a+56=-7 | | 6675=29x | | Y=29x+6675 | | 175=29x+6675 | | 25-19=3(x-9) | | 504=72(3x-20) | | -6(y+4)=0 | | 8=-logx | | 30=16-x | | 64x^2=r^2 | | 72=9(3x-20) | | 72=9(3-20) | | 7x-3(16-4x/2=-41 | | 88=9x+7 | | -3=4(8)+b | | 3/5g-1/3=-10/-3 | | 288x-16x^2=0 | | 2058=49(x+1) |

Equations solver categories